UTILIZATION PATTERN AND POTENTIAL OF GELAM WOOD (MELALEUCA CAJUPUTI POWELL) AS A FOUNDATION STRUCTURE - Ma’ruf, Muhammad Afief; Arifin, Yudi Firmanul; Asy’ari, Mufidah; Rusdiansyah (GEOMATE Journal, 2023)
Gelam wood (Melaleuca cajuputi Powell) is one of the essential raw materials for traditional foundations in Kalimantan, which is widely available along the wetlands. It plays an important role in supporting the construction of houses and other infrastructure in Indonesia. Consequently, there is a need for sustainable gelam wood cultivation in Kalimantan. Presently, it is not only used in the development of wetland stilt housing, but also for the interior of the house. Therefore, this study aimed to identify the pattern of using gelam wood as a foundation structure and its potential. The qualitative design method was used with an interview survey and literature review. The result showed that the patterns of using gelam wood as a foundation are as follows; 3-6 m length for simple buildings or 1-story houses, 7-10 m length for 2-story buildings or high-rise buildings, and 3-4 m length for road construction. The diameter of gelam wood used varies between 8-15 cm. Furthermore, the potential use is very large, where the need for residential foundations in Banjarmasin City is approximately 30000 m3 in 1 year, and an average of 14000-20000 are needed for 1 road construction project, not including those used for other structures.